Coral-Associated Actinobacteria: Diversity, Abundance, and Biotechnological Potentials - Mahmoud, Huda M.; Kalendar, Aisha A. (Frontiers in Microbiology, 2016)
Actinobacteria are widely distributed in terrestrial environments, where they are considered a significant source of bioactive compounds, mainly antibiotics. Marine Actinobacteria, particularly coral-associated Actinobacteria, have attracted attention recently. In this study, the abundance and diversity of Actinobacteria associated with Coscinaraea columna, Platygyra daedalea and Porites harrisoni, north of the Arabian Gulf were investigated. The corals of the Arabian Gulf, one of the world’s hottest seas, are thriving under extreme water temperatures that exceed 39°C during the summer. Similar water temperatures cause coral bleaching and death in other water bodies. For this reason, the corals of the Gulf are living models for investigating how corals in other settings may survive at the end of the current century. Different coral hosts have been found to harbor equivalent numbers of culturable Actinobacteria in their tissues but not in their mucus. However, different culturable actinobacterial communities have been found to be associated with different coral hosts. Differences in the abundance and diversity of Actinobacteria were detected between the mucus and tissue of the same coral host. In addition, temporal and spatial variations in the abundance and diversity of the cultivable actinobacterial communities were detected. In total, 19 different actinobacterial genera, namely Micrococcus, Brachybacterium, Brevibacterium, Streptomyces, Micromonospora, Renibacterium, Nocardia, Microbacterium, Dietzia, Cellulomonas, Ornithinimicrobium, Rhodococcus, Agrococcus, Kineococcus, Dermacoccus, Devriesea, Kocuria, Marmoricola and Arthrobacter, were isolated from the coral tissue and mucus samples. Furthermore, 82 isolates related to Micromonospora, Brachybacterium, Nocardia, Micrococcus, Arthrobacter, Rhodococcus and Streptomyces showed antimicrobial activities against representative Gram-positive and/or Gram-negative bacteria. Even though Brevibacterium and Kocuria were the most dominant actinobacterial isolates, they failed to show any antimicrobial activity, whereas less dominant genera, such as Streptomyces, did show antimicrobial activity. Focusing on the diversity of coral-associated Actinobacteria may lead to the discovery of novel antimicrobial metabolites with potential biotechnological applications.